Is Real Exchange Rate Hedging Motive Still Important in Determining Equity Home Bias? - Iryna Stewen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The majority of general equilibrium models of international portfolio holdings differ substantially in their modeling procedures but typically feature a term that captures the relationship between real exchange rate changes and relative, i.e. home vs. foreign, equity market returns. However, there is no consensus among the general equilibrium models on the sign of the exchange rate relative equity return relation. Recent empirical evidence focused on the US vis- -vis the rest-of-the world has not provided clear guidance in this respect. This paper fills this gap by taking a broader, international perspective. The evidence points to strong and significantly positive relative equity market return real exchange rate relations for non-EMU developed markets as well as emerging markets. The sign is as expected from standard, partial equilibrium models of home bias in international portfolio holdings. I further show that this evidence is strongly linked to countries trade and financial openness.
Keywords: G11; F21; F41; 330